Non-violence and social integration through extracurricular activities - Egerău, Anca Manuela (Technium Social Sciences Journal, 2025)
In the context of modern society, preventing violence and fostering social integration are priorities in youth development. Extracurricular activities represent an effective way to promote non-violence values and facilitate social integration by developing social skills, cooperation, and communication. This article explores the positive impact of extracurricular activities on young people’s behavior, contributing to the reduction of aggressive behavior and the increase of tolerance. The study analyzes examples of activities that have proven effective in promoting a culture of peace and social inclusion.